Too much of a good thing: a review of primary immune regulatory disorders - Tsilifis, Christo; Slatter, Mary A.; Gennery, Andrew R. (Frontiers in Immunology, 2023)
Primary immune regulatory disorders (PIRDs) are inborn errors of immunity caused by a loss in the regulatory mechanism of the inflammatory or immune response, leading to impaired immunological tolerance or an exuberant inflammatory response to various stimuli due to loss or gain of function mutations. Whilst PIRDs may feature susceptibility to recurrent, severe, or opportunistic infection in their phenotype, this group of syndromes has broadened the spectrum of disease caused by defects in immunity-related genes to include autoimmunity, autoinflammation, lymphoproliferation, malignancy, and allergy; increasing focus on PIRDs has thus redefined the classical 'primary immunodeficiency' as one aspect of an overarching group of inborn errors of immunity.The growing number of genetic defects associated with PIRDs has expanded our understanding of immune tolerance mechanisms and prompted identification of molecular targets for therapy. However, PIRDs remain difficult to recognise due to incomplete penetrance of their diverse phenotype, which may cross organ systems and present to multiple clinical specialists prior to review by an immunologist. Control of immune dysregulation with immunosuppressive therapies must be balanced against the enhanced infective risk posed by the underlying defect and accumulated end-organ damage, posing a challenge to clinicians. Whilst allogeneic haematopoietic stem cell transplantation may correct the underlying immune defect, identification of appropriate patients and timing of transplant is difficult. The relatively recent description of many PIRDs and rarity of individual genetic entities that comprise this group means data on natural history, clinical progression, and treatment are limited, and so international collaboration will be needed to better delineate phenotypes and the impact of existing and potential therapies. This review explores pathophysiology, clinical features, current therapeutic strategies for PIRDs including cellular platforms, and future directions for research.